Control method for improvement of power quality in single interlinking converter hybrid AC‐DC microgrids. Issue 4 (28th February 2021) - Baharizadeh, Mehdi; Karshenas, Hamid R.; Golsorkhi Esfahani, Mohammad S.
Abstract: Hybrid AC‐DC microgrids (HMGs) are formed by interconnecting AC microgrids (MGs) and DC microgrids via AC‐DC interlinking converters (ICs). In the islanded mode, apart from power sharing in a single MG, power sharing expansion throughout HMG is desirable. Conventionally, this is achieved by employing an IC control mechanism in coordination with the droop characteristics of sources. Because the conventional control strategy of IC relies on measuring the frequency variations in AC MG, accurate coordination necessitates a wide range of frequency deviation. Also, this strategy employs the current‐controlled method, which fails to accomplish superior voltage quality during load transients and in the presence of an unbalanced load obtainable by the voltage‐controlled method (VCM). An IC control strategy for single IC HMGs is proposed that does not require the measurement of frequency variation and employs VCM in the inner control loop. As a consequence, the power quality of AC MG is improved. The proposed control strategy is phase locked‐loop‐less. In addition, by supporting the related MG with the disconnection of sources in AC MG or DC MG, it provides a uniform control property. Time domain simulations and experimental results are provided to verify the efficacy of the proposed strategy.